Relationship between social cause, environment conservation and environmental attitude, towards promoting green purchasing behavior - Sondhi, Sundeep; Chawla, Udit; Iqbal, Hena (Serbian Journal of Management, 2023)
Irresponsible and imprudent usage of natural resources has presented a significant threat to the environment and its resources, contaminating them, and impeding their development. To mitigate this effect, responsible policies and practices must be adopted and implemented. One of the most successful strategies is to reduce our reliance on conventional items and replace them with green alternatives. However, insufficient information and expertise among consumers hamper their efforts to promote green products. Thus, it is critical to understand the factors influencing consumers’ behavior and intentions toward green products to increase their acceptance. The purpose of the study is to learn more about how caring about the environment, having a desire to make a positive impact, and having a positive attitude towards the environment can help encourage people to buy eco-friendly products. 549 responses were collected using Google form from India, China, Sri Lanka, Bangladesh, and Pakistan. Structural Equation Modelling was used to test the forming assumptions. It was found that the study supports the hypotheses and the constructs of social issues, environmental conservation, and mindset, are significantly associated with the green buying behavior of the consumers. Additionally, it was found that environmental attitude should be further integrated to reinforce these relationships.